Rise above : God can set you free from your weight problems forever - Shamblin, Gwen. (Nashville : T. Nelson, 2000)
Many people believe tht the success of Gwen Shamblin's book TH WEIGH DOWN DIET is unusual for a first-time author. She gives God all the glory for helping her bring His message of deliverance from the bondage of food anddieting to hundres of thousands all over the world. THE WEIGH DOWN DIET was only the skeleton of the formula for permanent weight loss. RISE ABOVEgoes beyond the principles of Weigh Down and searches the heart for the reasons people struggle or fail to lose weight. If you are battling the stronghold of overweight, this book will help you.
1. A Passionate People 1 -- 2. America Has a Crush on Food 7 -- 3. The Exodus Symbolism 23 -- 4. The Weigh Down[dagger] Explosion 44 -- 5. The Struggler 57 -- 6. Secret of the Prison 82 -- 7. Backstroking the Red Sea 115 -- 8. Hunger in the Desert 140 -- 9. Save Your Heart for Me 169 -- 10. Cloud and Fire 197 -- 11. Estranged from God 225 -- 12. Innocent in His Sight 241 -- 13. The Remnant 269 -- 14. Heaven's Kiss 303.
Includes bibliographical references (p. 339-340).
Keywords: Weight loss -- Religious aspects -- Christianity